Concise and efficient asymmetric homogeneous Janus membrane for high-performance osmotic energy conversion based on oppositely charged montmorillonite. (10th August 2022) - Hao, Jinlin; Ma, Shuhui; Hou, Yushuang; Wang, Weijie; Dai, Xi; Sui, Xin
Abstract: Inspired by the bioelectric phenomena of an electric eel, ion rectification systems with asymmetric properties have been applied to harvest osmotic energy. Recently, two-dimensional ion exchange membranes have shown remarkable potential for capturing nature energy from salinity gradients. To construct a highly efficient energy conversion system, asymmetric homogeneous membranes based on 2D materials need to be developed. Here, we wittily prepared an efficient ion exchange membrane, containing asymmetric lamellar nanochannels in oppositely charged montmorillonite membrane (MMT). By mixing concentrated (0.5 M) and diluted ionic solutions (0.01 M), the maximum output power density can peak at 2.1 W/m 2 and shows great stability in a wide range of pH. Moreover, theoretical calculations certify that the homogeneous asymmetric membrane could eliminate the concentration polarization. This work stands out the promise in the coupling of surface charge and space charge in the 2D-based asymmetric homogenous membrane for energy conversion. Graphical abstract: An asymmetric homogeneous Janus membrane based on polymer modified 2D materials is constructed for osmotic energy conversion, performing excellent ion transport property. Image, graphical abstract .